Multiple sclerosis in pregnancy- a case report - S, Sreelatha; Nayak, Vedavathy; Punneshetty, Sahana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Multiple sclerosis is primarily a disease of women in their reproductive years. Relapse rate decreases during pregnancy and rises after delivery. Pregnancy and puerperium have opposite effects on the course of the disease. The case presented is that of a second gravida who was a known case of multiple sclerosis. She was managed conservatively during pregnancy and puerperium.